Mucous membrane pemphigoid in a patient with chronic hepatitis B virus infection: A case report. Issue 20 (21st May 2021) - Chou, Christine Yi-Ting; Lin, Chi-Wei; Chen, Gwo-Shing; Huang, Ru-Yi
Abstract: Rationale: Mucous membrane pemphigoid (MMP) is a rare, autoimmune bullous disease that affects mucosal surfaces and skin. Early and aggressive treatment initiation may be warranted due to the risks of serious complications. However, it can be challenging to make an initial diagnosis. Viral infection such as hepatitis B virus (HBV) infection has been found to be associated with the formation of autoimmune bullous diseases. Patient concerns: The patient was a 43-year-old male with gingivitis and recurrent swelling over the neck, cheeks, lips, and eyelids. The patient presented at oral medicine, otolaryngology, plastic surgery, and ophthalmology sequentially, and was later referred to the rheumatology, dermatology, and family medicine departments. Recurrent hemorrhagic bullae on oral mucosa and skin scarring occurred 2 years after the onset of the initial symptoms. Diagnosis: Skin biopsy with direct immunofluorescence was performed under the suspicion of MMP. Lesional hematoxylin and eosin stain and perilesional direct immunofluorescence were consistent with MMP. Interventions: Systemic Prednisolone and topical corticosteroid were used to control the disease. Outcomes: A flare-up of hepatitis B developed as a result of systemic prednisolone use. The disease went through relapses and remissions. The patient is on low-dose prednisolone (5 mg/day) with a monthly outpatient visit in the family medicine department. Lessons: It would be useful for medical practitioners in different specialties to be alert of the heterogeneous presentations of MMP. Chronic HBV infection might be a risk factor for MMP. In patients with chronic HBV infection, treatment of MMP must be closely monitored for the risk of reactivation of HBV.